2022
DOI: 10.1111/bjd.20701
|View full text |Cite
|
Sign up to set email alerts
|

A 5-year retrospective review of skin adnexal tumours received at a tertiary dermatopathology service: implications for linked genetic diagnoses

Abstract: Background Skin adnexal tumours (SATs) comprise a diverse range of neoplasms, which are difficult to diagnose clinically. They present in paediatric and adult populations, and may be indicative of an underlying genetic syndrome. There is a lack of recent data on the presentation of these tumours in clinical practice in European populations. Objectives To characterize the clinical and pathological features of SATs received at a single tertiary centre over a 5-year period. Methods A retrospective health record a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 29 publications
(73 reference statements)
4
5
1
Order By: Relevance
“…16 The most frequent line of differentiation in our study was sweat gland (48.6%), followed by follicular (33.6%) and sebaceous (16.4%). This finding is similar to many of the previous studies done in the United Kingdom, 11 Turkey, 25 India, 7,11,[28][29][30] Nigeria, 9,20,23 and Egypt. 16 However, a study in India by Kala et al and Sinha et al, 18,27 a study in Nepal, 19 a study in Burkina Faso, 31 Morocco, 21 and a study in Slovakia 1 found hair follicle tumors to be the most common.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…16 The most frequent line of differentiation in our study was sweat gland (48.6%), followed by follicular (33.6%) and sebaceous (16.4%). This finding is similar to many of the previous studies done in the United Kingdom, 11 Turkey, 25 India, 7,11,[28][29][30] Nigeria, 9,20,23 and Egypt. 16 However, a study in India by Kala et al and Sinha et al, 18,27 a study in Nepal, 19 a study in Burkina Faso, 31 Morocco, 21 and a study in Slovakia 1 found hair follicle tumors to be the most common.…”
Section: Discussionsupporting
confidence: 92%
“…The study found the magnitude of skin adnexal tumors to be 2.8% of the total biopsies obtained during the 5-year period. This finding was higher than a previous study done in the United Kingdom, which reported 1.5% (of a total of 107,144 biopsy samples received), 11 and multiple Indian studies by Sonam et al 12 which found 0.12% magnitude of the total surgical pathology specimens, Thakuria et al 13 which found 0.62% (of a total of 4013 biopsies received), by Deka and Osman found the incidence of SATs to be 0.015% of all skin biopsies which were 1,221, 16 whereas lower than a study in Iran which reported 3.3% (of 30,000 pathology records). 17 The higher finding in our study might be because it studied the magnitude of all types of adnexal proliferations, not only neoplasms but also hamartomas, hyperplasias, and cysts arising from adnexal structures.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…The mean age range was 40.97±19.3 years in our study, which is similar to the study conducted by Yaqoob N et al [ 9 ], while the mean age was 28.2±9.45 years in a study published by Preeti et al, which is discordant with our findings [ 10 ]. Female gender predilection was noted in our study which is similar to the study conducted by Sam et al [ 11 ]. This is in contrast to the study done by Bansal A et al who cited male predominance [ 12 ].…”
Section: Discussionsupporting
confidence: 92%
“…In their valuable cross‐sectional 5‐year retrospective study published in this issue of the BJD , Cook et al . provide an excellent insight into adnexal tumours in a tertiary‐centre practice 1 …”
mentioning
confidence: 99%